REKONSTRUKSI KONSEP PENGAWASAN APARATUR SIPIL NEGARA DI DAERAH PADA PEMILIHAN KEPALA DAERAH SERENTAK 2024 PASCA PENGHAPUSAN KOMISI APARATUR SIPIL NEGARA - Badi’ah, Nurul Izzah Al; Hafiz, Si Yusuf Al (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The elimination of the State Civil Service Commission (KASN) through Law Number 20 of 2023 concerning the State Civil Service has a significant impact on the supervision of the neutrality of the State Civil Apparatus (ASN), especially ahead of the 2024 Simultaneous Regional Head Elections (Pilkada). Previously, KASN acted as an independent institution that supervised violations of ASN neutrality, as evidenced by the handling of cases in the previous Pilkada. In the absence of KASN, the obligation to maintain ASN neutrality is entirely borne by individual ASN and their respective agencies, giving rise to the potential for increased politicization of the bureaucracy and weak internal supervision. This study uses a normative approach by analyzing laws and regulations and other secondary data. The results of the study indicate the need for reconstruction of the concept of ASN supervision to address the vacuum of function left by KASN. The proposed solutions include the re-establishment of an independent institution, strengthening internal supervision mechanisms, and enforcing strict sanctions against violations. Increasing ASN understanding of neutrality rules and the commitment of all stakeholders are also key factors in creating effective supervision. This oversight reconstruction is expected to ensure the neutrality of ASN, prevent political intervention in the bureaucracy, and support the implementation of the 2024 Simultaneous Regional Elections that are fair and democratic. The integrity of ASN as professional government implementers is a key element in realizing a government that is free from conflicts of interest and corruption. Keyword: ASN supervision, regional elections, reconstruction Abstrak: Penghapusan Komisi Aparatur Sipil Negara (KASN) melalui Undang-Undang Nomor 20 Tahun 2023 tentang Aparatur Sipil Negara membawa dampak signifikan terhadap pengawasan netralitas Aparatur Sipil Negara (ASN), khususnya menjelang Pemilihan Kepala Daerah (Pilkada) Serentak 2024. Sebelumnya, KASN berperan sebagai lembaga independen yang mengawasi pelanggaran netralitas ASN, terbukti dari penanganan kasus pada Pilkada sebelumnya. Dengan tidak adanya KASN, kewajiban menjaga netralitas ASN sepenuhnya dibebankan kepada individu ASN dan instansi masing-masing, memunculkan potensi meningkatnya politisasi birokrasi serta lemahnya pengawasan internal. Penelitian ini menggunakan pendekatan normatif dengan menganalisis peraturan perundang-undangan dan data sekunder lainnya. Hasil penelitian menunjukkan perlunya rekonstruksi konsep pengawasan ASN untuk mengatasi kekosongan fungsi yang ditinggalkan oleh KASN. Solusi yang diusulkan meliputi pembentukan kembali lembaga independen, penguatan mekanisme pengawasan internal, serta penegakan sanksi yang tegas terhadap pelanggaran. Peningkatan pemahaman ASN terhadap aturan netralitas dan komitmen seluruh pemangku kepentingan juga menjadi faktor kunci dalam menciptakan pengawasan yang efektif. Rekonstruksi pengawasan ini diharapkan dapat memastikan netralitas ASN, mencegah intervensi politik dalam birokrasi, dan mendukung penyelenggaraan Pilkada Serentak 2024 yang adil dan demokratis. Integritas ASN sebagai pelaksana pemerintahan profesional menjadi elemen utama dalam mewujudkan pemerintahan yang bebas dari konflik kepentingan dan korupsi. Kata kunci: pengawasan ASN, pilkada, rekonstruksi.